Self-reported meal planning practices among households in the Tshwane North area, Gauteng - Lindiwe J. Ncube; Mashudu Manafe; Reno E. Gordon (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Meal planning is crucial for households to improve food choices and promote healthier eating habits.